The Effect Additional of Sodium Carbonate as Buffer in Utilization of Tofu Byproduct Lactic Acid Bacteria Fermentation as Basal Ration on Rumen Fermentation Bligon Goat during Lactation - Ihsani, Farkhan; Bachruddin, Zaenal; Noviandi, Cuk Tri; Yusiati, Lies Mira (Faculty of Animal Science, Universitas Gadjah Mada, ISSTAP 2017, 2017)
This study was aimed to evaluate the effect of NaHCO3addition as a buffer in fermented tofu waste concentrate by lactic acid bacteria on rumen fermentation characteristics of Bligon goats. The experiment was conducted in Jetak Village, Sidokarto, Godean, Sleman for 8 weeks. The experiment used eight lactating weight of bodyat 21 to 25 kg. The goats were divided into two treatments: control and treatment groups.The goats in control group wereoffered basal feed as much as 3% dry matter of body weight, consisted of 60% forage and 40% fermented concentrate feed. Goats were fed with the same basal feed in control group with the addition of NaHCO3 as much as 3% of the fermented concentrate feed (as fed). The examination was conducted to collect data on rumen fermentation characteristics of the collection-0 (t0) and 3 (t1) hours after feeding include: pH, VFAproduction, NH3 concentration, and microbial proteins producs. Data were analyzedstatistically with T-test. The results showed that the addition of buffer to the concentrate feed fermentation LAB significantly affect (P<0.05) pH, total VFA production (t0), and NH3 concentration (t1), but no significant effects were detectedon total VFA production (t1), microbial protein, and NH3 concentration (t0). It is concluded that NaHCO3addition as a buffer in fermented tofu waste concentrate able to maintain rumen pH in normal conditions, that the bio-fermentation process in the rumen optimally.